1999
DOI: 10.1046/j.1365-2141.1999.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of weak D and DVI red cells in D‐negative mixtures by flow cytometry: implications for feto‐maternal haemorrhage quantification and D typing policies for newborns

Abstract: Summary. Quantitation of feto-maternal haemorrhage (FMH) by flow cytometry (FC) has been shown to be more accurate than the Kleihauer-Bekte test. Fetal cells will be predominately of R 1 r or R 2 r phenotype, with antigen site numbers per cell (SPC) of between 9900 and 16 000. If the fetus is of weak D or partial D VI phenotype, fewer SPC will be present.Red cells from 20 adult weak D samples were mixed with rr red cells to give 1% mixes. Mixtures were stained and analysed by FC, using two different monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Lloyd‐Evans et al. (1999) found that weak D red cells with <1000 RhD sites per red cell were not detectable using quanti‐D (BTSN10 clone) flow cytometry.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lloyd‐Evans et al. (1999) found that weak D red cells with <1000 RhD sites per red cell were not detectable using quanti‐D (BTSN10 clone) flow cytometry.…”
Section: Discussionmentioning
confidence: 97%
“…However, the minimum volume of weak D red cells required for an immune response is not known. Lloyd‐Evans et al. (1999) suggested that the routine administration in the UK of a 500 IU dose of prophylactic anti‐D postpartum was probably sufficient to prevent anti‐D immunization when the FMH is much greater than 4 ml of weak D fetal red cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1996; Kumpel, 2001). This antibody also discriminates D‐variant RBC when they express more than 1000 D‐sites per red cell (Lloyd‐Evans et al. , 1999).…”
Section: Cell‐dyn Cd4000 Immunofluorescent Measurement Of Fmhmentioning
confidence: 99%
“…3) [86]. A further disadvantage of the directly labeled anti-D method is that it may not be able to distinguish weak D samples from D− cells [48,87]; this is not true for the indirect anti-D method [69]. In 1998, Davis et al [88] described an FC method using FITC anti-HbF for FMH quantitation.…”
Section: Detection and Quantitation Of Red Blood Cell Antigensmentioning
confidence: 99%